Sahih Al-Bukhari: Satu Analisis Tentang Kesahihan Hadis-hadis yang Terkandung di dalamnya - Mohsin, Udah (Jurnal Usuluddin, 1995)
This article describes the Hadith in Sahih al-Bukhari and Bukhari methodology in writing, as well as critiques from other scholars.